Spectrophotometric Determination of pKa of some Paracetamol Brands Collected from Pharmacies in Abidya City - Abdulrraziq Radad; Suad Omar; Marwa Abas (AlQalam Journal of Medical and Applied Sciences, 2024)
The experimental dissociation constant (pKa) value of paracetamol is presented in this work. Drugs’ dissociation constant (pKa), is one of their most significant physicochemical characteristics. When considering dosage form design and pharmacological analysis, it is extremely important. A UV-visible spectrophotometric technique was mainly employed to determine the pKa of paracetamol. Considering that spectrophotometric pKa determination yields the most accurate values, the spectrophotometric methods was used for the pKa determination. It was found that the pKa of paracetamol was 4.9, 9.9, and 10.5, then understanding a substance’s dissociation constant is crucial for a variety of applications and research fields. يتم تقدير قيمة ثابت التفكك للباراسيتامول في هذا العمل . يعد ثابت تفكك الأدوية أحد أهم خصائصها الفيزيائية والكيميائية. ومن وجهة نظر التحليل الصيدلاني وتصميم أشكال الجرعات، فهو مهم للغاية. تم استخدام تقنية مطياف الضوء المرئي و فوق البنفسجي بشكل رئيسي لتحديد ثابت تفكك الأدوية للباراسيتامول. طرق التحليل الطيفي اعطت قيم عالية الدقه لثابت تفكك الأدوية، وقد وجد أن ثابت تفكك الأدوية للباراسيتامول ترواحت من 4.9، 9.9 و10.5. وهنا يعد فهم ثابت تفكك المادة أمرًا بالغ الأهمية لمجموعة متنوعة من التطبيقات ومجالات البحث